Simulation of the electromagnetic field response of a horizontal ring electric dipole antenna in planarly homogeneous layered media - Dahy, E. (American Scientific Publishers, 2017)
Sea bed logging (SBL) is a direct and remote application of control source electromagnetic (CSEM) method to detect the hydrocarbon wells beneath the subsurface mostly in offshore conditions. In this method, electromagnetic waves are used to detect the resistivity contrast between the various sediments in the subsurface. In this work, a new design of antenna is used as the source of Electromagnetic (EM) waves, this antenna is complete circle located horizontally above sea bed at a height of 30 m. Maxwell Equations solved in two modes (poloidal and toroidal modes) to determine the electromagnetic waves propagation in all directions. The significant waves from the propagating antenna are symmetry for up and down going waves. The stronger the down going EM waves the deeper they penetrate the subsurface and get reflected back to the sea floor by resistive layers in the subsurface. This would help in detecting the resistive layer under seabed. Numerical solutions of the equations are given in relation to variations in antenna frequencies. The performance of the antenna is analyzed for frequencies of 0.01 Hz to 10 Hz. Copyright © 2017 American Scientific Publishers All rights reserved Printed in the United States of America.